A quantitative ethnobotanical approach to assess knowledge richness on the use of plants among the Santal Medicine Men of Birbhum district, West Bengal, India - Pradhan, Bandana; Mondal, Swarnendu (Ethnobotany Research and Applications, 2023)
Background: Documentation of folk tradition on the use of medicinal plants is being carried out by the ethnobotanist from different parts of the world. The present study aims to measure medicinal plant use-knowledge among the Santal tribal people of Birbhum district. In terms of quantitative ethnobotany, this study is the first attempt from the district of Birbhum, West Bengal. The quantitative analysis in this research work identifies potential medicinal plants and plants which demand priority for immediate conservation. Methods: This ethnomedicinal survey was done in the tribal pockets of Birbhum district from August 2019 to August 2021. In this study 31 tribal informants were selected employing purposive sampling method and interrogated by throwing semi-structured questionnaires. In-situ (Inventory interview, guided tour) and ex-situ (visual stimuli, photographic documentation of preserved herbal drugs along with questionnaire) methods were applied during data collection. Free and Prior Informed Consent (PIC) has been taken. Recorded data were analysed by conventional (qualitative) and quantitative ethnobotanical (Informants Consensus Factor, Relative Frequency of Citation and Fidelity Level) techniques. Finally, the IUCN Red List was scrutinized for the global status of the documented species and conservation aspects were highlighted based on quantitative techniques. Results: A total of 40 ethnomedicinal plant species were recorded which belong to 33 families and 40 genera were recorded. These plants were formulated in curing about 34 different diseases and ailments of human and veterinary animals. Herbaceous plants (35%) were mostly used in remedy preparations. Decoction (N=22) is the preferred form of medication followed by poultice and ointment (N = 11), massage (N = 4), Chewing (N = 1), powder (N = 1). Commonly used plant parts were underground parts like roots, rhizome and pseudobulb (N=20) followed by leaf (N=10), stem bark (N=7), flower (N=2), whole plant (N=1). Fic value of 12 disease categories range from 0.31-0.764, among them respiratory disorders got the highest value. Quantitative analysis following Relative Frequency of Citation(RFC) and Fidelity Level(FL%) indices showed that some taxa were getting maximum Fidelity Level (100%) and RFC (1), namely Euphorbia fusiformis, Madhuca longifolia var. latifolia, Cleistanthus collinus, etc. The IUCN status of 40 reported medicinal plant species showed 5 % species are presently Vulnerable (Jatropha nana, Cleistanthus collinus),15 % Least Concern (Eclipta prostrata, Hellinia speciosa, Litsea glutinosa, Pterospermum acerifolium, Rivea hypocrateriformis, Woodfordia fruticosa), while the status is unknown for 80% of the documented species. Conclusion: The study concluded that some important ethnomedicinal species like Woodfordia fruticosa, Premna herbacea, Pterospermum acerifolium, Ruellia suffruticosa, Cleistanthus colliinus, Hellinia speciosa, etc. are frequently used in tribal medicine of the Birbhum district as identified on basis of their high RFC and FL values. It caters for the scope of further study with these plants in the line of pharmacognosy, phytochemistry and pharmacology. There is also an urgent need to acknowledge Local Knowledge Holders and preservation of associated phytoresources of the study area which has not been addressed till date. Medicinal plant species such as Jatropha nana and Cleistanthus collinus are Vulnerable and many others could be included in the threatened category in near future due to overexploitation. So conservation priority and conservation measures should be set up through in-depth study of diversity and population of the medicinal plants which are unsustainably harvested. Keywords: Ethnomedicinal flora, Birbhum district, High Fidelity, crude drug, pharmacognosy, IUCN status, conservation